The Paradox of the Sufi Sultanate: Charismatic Scaffolding and Epistemic Erasure in Islamic Statecraft - Hidayat, Muhammad Syaiful Bahri; Ulum, Muhammad Nashrul (Yayasan Pesantren Mahasiswa An-Nur, 2025)
History records recurring instances where Sufi brotherhoods transitioned into territorial states, notably in the Safavid Empire, the Sokoto Caliphate, and North African resistance movements. However, current scholarship often conflates the mystical identity of founders with the administrative reality of these polities, assuming a continuity of